An Efficient Approach to Aromatic Aminomethylation Using Dichloromethane as Methylene Source - Ostacolo, Carmine; Di Sarno, Veronica; Musella, Simona; Ciaglia, Tania; Vestuto, Vincenzo; Pepe, Giacomo; Merciai, Fabrizio; Campiglia, Pietro; Gomez Monterrey, Isabel M.; Bertamino, Alessia (Frontiers in Chemistry, 2019)
Ultrasound-promoted N-aminomethylation of indoles can be achieved in basic medium using sodium hydride and dichloromethane (DCM) as C1 donor source. This innovative amino methylation protocol results in good to excellent yields of multifunctional indole derivatives. The procedure is also applicable to other aza-heterocyclic compounds and, interestingly, affords direct access to aminomethyl-substituted aryl alcohols.